(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Hydrodynamic journal bearings are critical components in high-speed rotating machinery, where their performance is strongly influenced by thermal effects generated due to viscous shearing of the lubricant. This paper investigates the impact of thermal variations on the load-carrying capacity and stability characteristics of hydrodynamic journal bearings. Temperature rise within the lubricant film alters viscosity distribution, pressure development, and film thickness, thereby affecting bearing stiffness, damping coefficients, and dynamic stability limits. A thermo-hydrodynamic framework is employed to analyze the coupled effects of heat generation, heat dissipation, and fluid–structure interaction on bearing behavior under varying operating conditions. The results demonstrate that increased thermal gradients lead to a reduction in load capacity and can significantly influence the onset of instability phenomena such as oil whirl and oil whip. The study highlights the necessity of incorporating thermal considerations in bearing design and performance prediction to ensure reliable and stable operation of rotating systems.